Dielectric and mechanical properties of poly(butylene succinate) thin film composites incorporated with barium strontium titanate powder. Issue 174 (1st September 2016) - Nootsuwan, Nollapan; Plungpongpan, Kittichin; Wattanathana, Worawat; Koonsaeng, Nattamon; Laobuthee, Apirat; Manuspiya, Hathaikarn
ABSTRACT: High dielectric constant barium strontium titanate (Ba0.7 Sr0.3 TiO3 or BST) powder was prepared by sol-gel method for using as a filler in poly(butylene succinate) (PBS) composite with 0–3 connectivity system. Moreover, thermal and dielectric properties of poly(butylene succinate) integrated with BST powder were studied. The results showed the success of improving thermal stability and dielectric constant of poly(butylene-succinate) by increasing amount of BST powder. Therefore, the prepared PBS-BST composite thin films with good dielectric properties, flexibility, and processability could be applicable for the thin film capacitor for high-frequency electronic devices.